Foreign trade between Ukraine and the EU - Belinska, Yanina Vasylivna; Shevchuk, Oleksandra Ihorivna; Белінська, Яніна (Словацький університет сільського господарства в Нітрі, Словаччина, 2023)
The article examines the trends in the development of trade relations between Ukraine and the EU. The positive changes that have taken place in European-Ukrainian relations in recent years are outlined. The dynamics and structure of exports and imports of goods and services are analysed, and the trends that have occurred over the past fve years are identifed. The place of Ukraine in the structure of EU foreign trade is considered. It is revealed that the foreign trade turnover between Ukraine and the EU is aﬀected by the war. The main problems that hinder Ukraine‘s integration into the EU trade system are summarised and recommendations for their solution are provided.

У статті досліджено тенденції розвитку торгових відносин між Україною та ЄС. Окреслено позитивні зміни, які відбулися в європейсько-українських відносинах за останні роки. Проаналізовано динаміку та структуру експорту та імпорту товарів і послуг, визначено тенденції, що мають місце за останні п’ять років. Розглянуто місце України в структурі зовнішньої торгівлі ЄС. Виявлено, що на зовнішньоторговельний оборот між Україною та ЄС впливає війна. Узагальнено основні проблеми, що заважають інтеграції України в торговельну систему ЄС, та надано рекомендації щодо їх вирішення.
Keywords: EU foreign trade; European integration; Ukraine‘s trade relations with the EU; competitiveness; geospatial structure; product structure; partner countries; зовнішня торгівля ЄС; євроінтеграція; торговельні відносини України з ЄС; конкурентоспроможність; геопросторова структура; товарна структура; країни-партнери